Antibacterial Activity of Neem Extract and its Green Synthesized Silver Nanoparticles against Pseudomonas aeruginosa - P. Senthilkumar (Journal of Pure and Applied Microbiology, 2018)
Azadirachta indica, generally called as neem, margosa or Indian lilac is an Indian subcontinent native species, it ie well known for its various bioactivity In this study, neem leaves were collected and extracted. The extract was subjected for TLC and antibacterial activity against Pseudomonas aeruginosa. The extract was subjected for green synthesis of silver nanoparticles and it was able to reduce silver to silver nanoparticle of size around 65nm. The silver nanoparticle was also exhibiting antibacterial activity against P.aeruginosa.